Au Clusters on Pd Nanosheets Selectively Switch the Pathway of Ethanol Electrooxidation: Amorphous/Crystalline Interface Matters. Issue 19 (2nd April 2021) - Lv, Fan; Zhang, Weiyu; Sun, Mingzi; Lin, Fangxu; Wu, Tong; Zhou, Peng; Yang, Wenxiu; Gao, Peng; Huang, Bolong; Guo, Shaojun
Abstract: The development of ethanol electrooxidation catalysts with high activity and robust stability is essential for the commercialization of direct ethanol fuel cells. However, because of their low C1 selectivity, the electrocatalytic efficiency of catalysts for complete ethanol oxidation is still far from satisfying. Herein, a novel 2D PdAu heterogeneous catalyst for enhancing C1 selectivity to achieve highly efficient ethanol oxidation through phase and interphase engineering is designed. It is found that owing to the plentiful amorphous/crystalline interphases, the selectivity of C1 pathway on PdAu heterocatalyst can be improved up to 33.2% at a low potential, 10.4 times higher than commercial Pd/C (3.2%). Furthermore, 89.1% of initial mass activity of PdAu HNS can be retained after the accelerated degradation test of 2000 potential cycles, much higher than those of Pd NS (39.3%), commercial Pd/C (34.4%), and Pt/C (11.4%). The CO stripping and in situ Fourier transform infrared experiments reveal that 2D PdAu heterocatalyst, with intricate design of the amorphous Pd domain and the crystalline Au cluster interface, has better antipoisoning properties and stronger CC bond cleavage ability than pure Pd nanosheets. Density functional theory calculations further demonstrate that the introduction of Au clusters switches on the electroactivity of amorphous Pd as the electron pump to accomplish the complete oxidation of ethanol, in which the selectivity for C1 pathway is significantly boosted whereas the typical C2 pathway is substantially blocked. Abstract : Novel of 2D PdAu heterophase nanosheets (PdAu HNS) with abundant amorphous Pd domain/crystalline Au cluster interphases are reported to achieve superior electrocatalytic performance for the ethanol oxidation reaction (EOR). In particular, the C1 pathway selectivity of PdAu HNS for EOR is improved by ten times compared with that of commercial Pd/C.